The impacts of the financial performance indicators on the stock returns in the Chinese Stock Market - Cheng, Zixuan (2020)
The study is to explore the impacts of the financial performance indicators on Return on Asset (ROA), Return on Equity (ROE), Profit Margin (PM), Quick Ratio (QR), Debt to Asset Ratio (DER), Earnings per Share (EPS), Total Asset Turnover (TATO) and Economic Value Added (EVA) against dependent variable on the stock returns. The study noticed ROA, ROE, PM, EPS and TATO have significant effect on the stock return in case of consumer goods sector. In case of industrials sector, there also has negative relationship between ROA and the stock return. Compared to FEM, there are few variables that have a significant impact on stock returns using REM in case of energy, health care, materials and utilities sectors. The results also indicated TATO and PM affect positively stock returns in case of energy sector. However, ROA has no significant effect on the stock returns in case of sectors selected using REM, while EPS has positive effect on the stock returns in case of utilities and technology sectors. Meanwhile, there are positive impacts of ROE and economic value added (EVA) on the stock return in case of materials sector. Also, EVA has a positive significant impact on stock return in case of health care sector.